Evaluation of implementation of Adiwiyata SMPN Program Tanjungpinang City Riau Islands Province - Herman; Sujanto, Bedjo; Suryadi (Technium Social Sciences Journal, 2020)
The purpose of this research is to evaluate the implementation of the Adiwiyata program at SMPN Kota TanjungPinang, Riau Islands Province, where there are many problems that occur in the city of Tanjung Pinang, while the schools used as research sites are SMP Negeri 7, SMP Negeri 4, and SMP Negeri 2. which is in the West Tanjungpinang district. This study is an evaluation of the Adiwiyata Program Implementation. The main objective of this program evaluation research is to use a qualitative approach. Data collection techniques used include: (1) Interview (2) Observation, (3) Documentation. The data analysis technique was performed using an interactive model and Miles and Huberman (1984), where the analysis was carried out continuously. This model includes three activities, namely data reduction, data display and conclusion drawing / verification. Based on the research objectives described in CHAPTER IV, which aims to determine the implementation of the Adiwiyata Program Evaluation at SMPN Tanjungpinang City, Riau Islands Province. So the conclusions obtained by researchers related to this research are components that are evaluated in the form of interviews and observations, namely, legal basis, adiwiyata program principles (Context Aspect), Adiwiyata Program Target (Input Aspect), Adiwiyata Program Development (Process Aspect), Mechanism Adiwiyata Development and Adiwiyata Program Award (Product Aspect).